SAT0246 TARGETING JAK/STAT PATHWAY IN TAKAYASU'S ARTERITIS. (2nd June 2020) - Régnier, P.; Le Joncour, A.; Maciejewski-Duval, A.; Desbois, A. C.; Comarmond, C.; Rosenzwajg, M.; Klatzmann, D.; Cacoub, P.; Saadoun, D.
Abstract : Background: Takayasu's arteritis (TAK) is a large vessel vasculitis (LVV) in which the aorta and its main branches are greatly inflamed, leading to wall thickening, fibrosis, stenosis and to artery occlusion(1). The disease is more common in women mostly between 20 and 30 years old. TAK has a high morbidity rate: 50% of patients will relapse within 10 years after diagnosis(2, 3). This inflammation is essentially mediated by infiltration with macrophages and pro-inflammatory Th1/Th17 effector subsets(4–8). But the mechanisms behind these phenomena are essentially unknown. TAK is mainly treated with non-specific steroids(1) which are associated with potential side effects when used for a long-time course. Objectives: Our work aims to explore the involvement of JAK/STAT signaling pathway and its downstream biological cascades in pro-inflammatory T cells differentiation and disease activity of TAK. Plus, our work allows to consider targeting the JAK/STAT pathway in TAK using JAK inhibitors (JAKinibs). Methods: We analyzed transcriptome of FACS-sorted CD4+ and CD8+ T cells from healthy donors (HD) and TAK, using differential gene, pathway and network analysis. Then, we assessed in vitro and in vivo effects of JAKinibs in TAK by flow cytometry (FC). Results: Transcriptome analysis showed hundreds of significantly dysregulated genes/pathways for CD4+ and CD8+ samples between HD and TAK. Among these, we noticed in TAK a great enrichment for pathways linked to type I and II interferons (IFN), JAK/STAT and cytokines/chemokines-related signaling. We confirmed by RT-qPCR the upregulation of a type I IFN-specific gene signature in TAK T cells as compared to HD. Using genes coming from the previous pathways, we constructed networks connecting them according to their respective protein interactions. This representation showed for both CD4+ and CD8+ T cells that JAK and STAT genes were densely connected, thus representing core genes/proteins in the TAK physiopathology. We then performed in vitro cell cultures of PBMCs from HD or TAK supplemented with Ruxolitinib (JAK1/2 inhibitor) or PBS. We observed by FC that JAKinibs significantly induced in TAK CD4+ and CD8+ T cells reduction of CD25 expression, decrease of Th1/Th17 pro-inflammatory cells and increase of Tregs. Next, we followed by FC 3 TAK (refractory to conventional treatments) treated with JAKinibs. We also observed in their PBMCs a reduction of CD25 expression by CD4+ T cells, a decrease of Th1 and Th17 cells and an increase of Tregs, accompanied by an increase of the Tregs/Teffs ratio. JAKinibs also decreased C-Reactive Protein level, NIH score and co-administered steroids doses (present before JAKinibs introduction) in these 3 in vivo-treated TAK. Conclusion: JAK/STAT signaling pathway is critical in the pathogenesis of TAK and JAKinibs may be promising in its treatment. References: [1]F. Numano, M. Okawara, H. Inomata, Y. Kobayashi, The Lancet. 356, 1023–1025 (2000). [2]C. Comarmond et al., Circulation. 136, 1114–1122 (2017). [3]A. Mirouse et al., J. Autoimmun. 96, 35–39 (2019). [4]C. M. Weyand, J. J. Goronzy, Nat. Rev. Rheumatol. 9, 731–740 (2013). [5]C. M. Weyand et al., Clin. Immunol. 206, 33–41 (2019). [6]D. Saadoun et al., Arthritis Rheumatol. 67, 1353–1360 (2015). [7]T. Mirault, H. Guillet, E. Messas, Presse Médicale. 46, e189–e196 (2017). [8]D. P. Misra, S. Chaurasia, R. Misra, Autoimmune Dis. 2016, 1–8 (2016). Disclosure of Interests: Paul Régnier: None declared, Alexandre Le Joncour: None declared, Anna Maciejewski-Duval: None declared, Anne-Claire DESBOIS: None declared, Cloé Comarmond: None declared, Michelle Rosenzwajg: None declared, David Klatzmann Consultant of: ILTOO Pharma, Patrice cacoub: None declared, David Saadoun: None declared